Env from EIAV vaccine delicately regulates NLRP3 activation via attenuating NLRP3-NEK7 interaction. - Xing Guo; Cong Liu; Yuhong Wang; Hongxin Li; Saiwen Ma; Lei Na; Huiling Ren; Yuezhi Lin; Xiaojun Wang (PLoS Pathogens)
The current equine infectious anemia virus (EIAV) vaccine causes attenuation of the inflammatory response to an appropriate level, compared to that produced by virulent EIAV. However, how the EIAV vaccine finely regulates the inflammatory response remains unclear. Using a constructed NLRP3-IL-1β screening system, viral proteins from two EIAV strains (the attenuated vaccine and its virulent mother strain) were examined separately. Firstly, EIAV-Env was screened to direct binding P2X7 (R) with notable K+ efflux trans-cellularly. Secondly, EIAV-Env was found to bind NLRP3 and/or NEK7 to trigger aggregation of NLRP3-NEK7 to form NLRP3-NEK7 complex in cells. Comparison of the two strains, we observed a significant reduction on vaccine-Env-initiated NLRP3-NEK7 complex formation, with no difference in Env triggering P2X7 (R)-mediated ion fluxes. Thirdly, reciprocally mutation on four stable varied amino acids between two strains produced an anticipated outcome on NLRP3-IL-1β-axis activation. As the attenuated vaccine was shown evolved as a natural quasispecies of the virulent EIAV, its precise and adaptable regulation via spatial proximity-dependent intracellular activation might present a "win-win" virus-host adaption, offering an alternative strategy on envelop-based vaccines development.